2018
DOI: 10.1016/j.clinthera.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Prevalence of Emergency Department Patient Substance Use

Abstract: There are sex-specific differences in prevalence of patients presenting with substance use in the ED setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Although hospitalization rates for AH increased in the preceding years, the change between 2019 and 2020 outpaced the previous increase of 5.5% per year. Consistent with previous data about the shifting age demographic of AH and higher rates of binge drinking and hospital utilization by men (Cannon et al, 2018), Marlowe and colleagues found that male patients under 40 years of age had the highest rate of increase in hospitalizations for AH (23% increase in 2020). Hospitalization rates for AH increased 14.9% in women in 2020 compared to 2019, which is consistent with the reported increase in incidence and prevalence of alcohol‐related liver disease (ALD) in women (Mellinger et al, 2018).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Although hospitalization rates for AH increased in the preceding years, the change between 2019 and 2020 outpaced the previous increase of 5.5% per year. Consistent with previous data about the shifting age demographic of AH and higher rates of binge drinking and hospital utilization by men (Cannon et al, 2018), Marlowe and colleagues found that male patients under 40 years of age had the highest rate of increase in hospitalizations for AH (23% increase in 2020). Hospitalization rates for AH increased 14.9% in women in 2020 compared to 2019, which is consistent with the reported increase in incidence and prevalence of alcohol‐related liver disease (ALD) in women (Mellinger et al, 2018).…”
supporting
confidence: 76%
“…Although hospitalization rates for AH increased in the preceding years, the change between 2019 and 2020 outpaced the previous increase of 5.5% per year. Consistent with previous data about the shifting age demographic of AH and higher rates of binge drinking and hospital utilization by men (Cannon et al, 2018), Marlowe and colleagues found that male patients under 40 years of age had the highest rate of increase in hospitalizations for AH (23% increase in 2020).…”
supporting
confidence: 71%
“…The selected articles discuss the experience of pain, pain treatment, opioid prescribing patterns, and prevalence of opioid misuse in women and men. [20][21][22][23][24] Dr. McGregor continues to spotlight our efforts to inform our readership about sex and gender differences in presenting symptoms, use of services, and treatment outcomes. 25,26 In the late 1960s and 1970s, my colleagues and I studied links between the phases of the menstrual cycle and drug effects, binge drinking, and visits to emergency departments (EDs).…”
Section: This Month's Updatementioning
confidence: 99%
“…In the article in this Update by Cannon and colleagues on the prevalence of ED visits because of substance use, alcohol use was the most common reason for both men and women. 23 They found that female ED users were younger than their male counterparts and likely to still be menstruating. Our own finding was that alcohol misuse, particularly binge drinking, was significantly more common when women were in the premenstrual phase of their cycle.…”
Section: This Month's Updatementioning
confidence: 99%
“…In their study, Sex Differences in Prevalence of Emergency Department Patient Substance Use, Dr. Robert Cannon and colleagues 9 determined the sex-specific prevalence of substance use and misuse in an emergency department patient population. The understanding that opioids were the second most common substance, after alcohol, in patients discharged with a substance use disorder allows the ability to explore patient sex in conjunction with preferred substance use to inform future programs designed at prevention and treatment.…”
mentioning
confidence: 99%